Assessment of the viral safety of antivenoms fractionated from equine plasma - Burnouf, Thierry (2004)
Antivenoms are preparations of intact or fragmented (F(ab')2 or Fab) immunoglobulin G (IgG) used in human medicine to treat the severe envenomings resulting from the bites and stings of various animals, such as snakes, spiders, scorpions, or marine animals, or from the contact with poisonous plants. They are obtained by fractionating plasma collected from immunized horses or, less frequently, sheep. Manufacturing processes usually include pepsin digestion at acid pH, papain digestion, ammonium sulphate precipitation, caprylic acid precipitation, heat coagulation and/or chromatography. Most production processes do not have deliberately introduced viral inactivation or removal treatments, but antivenoms have never been found to transmit viruses to humans. Nevertheless, the recent examples of zoonotic diseases highlight the need to perform a careful assessment of the viral safety of antivenoms. This paper reviews the characteristics of equine viruses of antivenoms and discusses the potential of some manufacturing steps to avoid risks of viral contamination. Analysis of production parameters indicate that acid pH treatments and caprylic acid precipitations, which have been validated for the manufacture of some human IgG products, appear to provide the best potential for viral inactivation of antivenoms. As many manufacturers of antivenoms located in developing countries lack the resources to conduct formal viral validation studies, it is hoped that this review will help in the scientific understanding of the viral safety factors of antivenoms, in the controlled implementation of the manufacturing steps with expected impact on viral safety, and in the overall reinforcement of good manufacturing practices of these essential therapeutic products.